Lecture: “First Aid to the Population in Case of Heat and Sunstroke during Accidents, Catastrophes, Natural Disasters and Terrorist Attacks” of the Subject “Life Safety” for Humanitarian and Technical Universities - KA, Shapovalov; LA, Shapovalova (Journal of Community Medicine and Health Solutions, 2024)
To prepare the population for first aid in case of heat and sunstroke in the context of global warming, algorithms for the basics of didactics of the educational topic “Heat and sunstroke” of the subject “Life safety” are proposed. The 30-year experience of teaching the subject in humanitarian state educational institutions of higher professional education of a non-medical profile in Syktyvkar is summarized. For each of the considered educational issues, a brief summary of the material presented is given.